FORGIVING THE UNFORGIVABLE: LANGUAGE POWER IN POLITICAL COMMUNICATION BETWEEN INDONESIA AND TIMOR-LESTE (Qualitative Research on Conflict Resolution over Human Rights Violations in East Timor, Before and After Referendum of 1999) - Djoko Utomo; Udi Rusadi; Ridzki Rinanto Sigit (International Journal of Social Science, 2023)
The conflict that occurred between Indonesia and Timor-Leste (Timor Timur) after the Popular Consultation was a conflict of power or a power struggle. This power struggle resulted in gross human rights violations. To resolve this conflict, in 2005 the Indonesian Timor-Leste Truth and Friendship Commission (KKP) was formed. Researchers assume that language can be used in conflict resolution. So the aims of this study are (1) to reveal the meaning of the text in Per Memoriam Ad Spem in constructing human rights violations in Timor-Leste in 1999, before and after the Popular Consultation. (2) Explaining the power of language in the construction of reports on human rights violations and conflict resolution in Per Memoriam Ad Spem, so that an agreement is reached that should not be forgiven to be forgiven. Van Dijk's discourse theory, Derrida's theory of deconstruction, and Bourdieu's theory of language & power, all three are related to language and power. These three theories are used as a basis for dissecting the phenomenon of this research. This study uses a critical constructionism paradigm, a type of qualitative research, and an interpretive approach. The findings of this study are that the strength of the Indonesian language as the primary working language has a very extraordinary impact. Textually, in the macro, meso, and micro dimensions, through language, political communication has been constructed which leads to the establishment of reconciliation between parties in power, which should deconstruct human rights violations. The parties with their power discourse can melt down, so that gross violations of human rights, which should not be forgiven, become forgiven. This is in line with Derrida's idea of true forgiveness or unconditional forgiveness, namely forgiving the unforgivable